Tradisi Bamandi-mandi Tujuh Bulanan dalam Perspektif Manajemen Pendidikan Islam - Siti Nur Syafa’ah; Zulfa Jamalie (MAN 4 Kota Pekanbaru, 2026)
The Bamandi-mandi tradition within the Banjar community is often perceived merely as a ceremonial ritual, overlooking the organized process of value transmission embedded within it. This study aims to examine the practices of informal Islamic education in the Bamandi-mandi tradition through the lens of educational management, specifically the POAC framework (Planning, Organizing, Actuating, and Controlling). This research employs a qualitative approach combining library research as the primary data source with narrative interviews to strengthen contextual analysis. The findings reveal that this tradition implicitly implements managerial functions: from the collaborative timing of the event (planning) and the distribution of social roles (organizing), to the actualization of religious values through prayer and tawakkal (actuating), and the preservation of values by community elders (controlling). These findings emphasize that local traditions are not merely cultural symbols but systematic informal educational instruments for internalizing Islamic morality. Theoretically, this study contributes to the development of Islamic education management by extending the application of the POAC framework to culturally embedded informal educational practices within local traditions. This study demonstrates that management theory provides a compelling perspective for uncovering the profound meanings within local wisdom.